2023
DOI: 10.1002/ece3.10144
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prey abundance and fisheries on the survival, reproduction, and social structure of killer whales (Orcinus orca) at subantarctic Marion Island

Abstract: Most marine apex predators are keystone species that fundamentally influence their ecosystems through cascading top-down processes. Reductions in worldwide predator abundances, attributed to environmental-and anthropogenic-induced changes to prey availability and negative interactions with fisheries, can have far-reaching ecosystem impacts. We tested whether the survival of killer whales (Orcinus orca) observed at Marion Island in the Southern Indian Ocean correlated with social structure and prey variables (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 83 publications
(151 reference statements)
0
8
0
Order By: Relevance
“…RF model results indicated that the occurrence of echolocation clicks fluctuated with the increase in number of killer whales sighted around Marion Island, supporting the notion that the PEIs killer whales have complex foraging strategies driven by their adaptive social structure [10,22,28]. The number of killer whales (when eight or more animals were in the vicinity of Marion Island) resulted in an increase in the occurrence of social calls, which validates the dependence of large groups on acoustics for communication [35].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…RF model results indicated that the occurrence of echolocation clicks fluctuated with the increase in number of killer whales sighted around Marion Island, supporting the notion that the PEIs killer whales have complex foraging strategies driven by their adaptive social structure [10,22,28]. The number of killer whales (when eight or more animals were in the vicinity of Marion Island) resulted in an increase in the occurrence of social calls, which validates the dependence of large groups on acoustics for communication [35].…”
Section: Discussionmentioning
confidence: 74%
“…Diel vocalizing behaviour of killer whales indicated a strong pattern for most seasons, a suggestion of adaptive and diverse vocalizing patterns probably linked to their dynamic foraging behaviour, social structure and activities [ 1 , 7 , 10 , 27 , 32 , 33 ]. These killer whales produced equally high rates of echolocation clicks during daytime and night-time in autumn and spring, but produced higher click rates at night in summer, which indicates that they might have been hunting around the PEIs when the SES abundance was high [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations